PENGARUH PENERAPAN MODEL CONCEPT SENTENCE TERHADAP KETERAMPILAN MENULIS KARANGAN DESKRIPSI SISWA KELAS IV SD - Nurhaedah, Nurhaedah; Suarlin, Suarlin; Novitasari, Ririn Nur (Universitas Negeri Makassar, 2023)
This research was conducted based on the problem of the low skills writing descriptive essays for students. The data in the study were collected using documentation, observation sheets and objective tests given before and after the implementation of learning. Inferential the results of the descriptive analysis showed that the aplication of the concept sentence model was very effective. The results of the inferential analysis using the independent sample t-test showed that there were differences in posttest results between the experimental and control classes, which means an increase in students’ descriptive essay writing skills in the experimental group is better than the control group. Control supported by N-gain the experimental group is higher than the control group which get the medium category. So it can be concluded that (1) the learning process by applying the concept sentence model takes place very effectively. (2) student test results showed an increase in students’ descriptive essay writing skills in learning. (3) there is an effect of application of the concept sentence model on the skills of writing descriptive essays for fourth grade students of SD Inpres 12/79 Bana Kabupaten Bone.